O que é a fenomenologia? uma leitura da Conferência Über Phänomenologie, de Adolf Reinach - Fernandes, Gabriel de Vitto (2023)
This dissertation explores Adolf Reinach's phenomenology and his ontological attitude, in comparison with Husserl's phenomenology, based on the Über Phänomenologie conference and related texts. The study investigates the nature of Reinach's phenomenology, analyzing the fundamental themes of the phenomenological method and his theory of states of affairs, that is, by emphasizing the analysis of essences and their divergence in relation to Husserl's intentional consciousness, Reinach presents a realistic perspective. The research also explores the ontology of states of affairs, highlighting their peculiarity, as subsisting ideal objects. Ultimately, we will seek to point out how Reinach's phenomenology offers an alternative approach to transcendental idealism, providing relevant insights for understanding contemporary phenomenology